PENGARUH JENIS FORMULA DAN TAKARAN PUPUK ORGANIK PLUS TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DI POLYBAG - Syafrullah, Syafrullah; Amir, Nurbaiti; Syafarudin, Syafarudin (Universitas Muhammadiyah Palembang, 2016)
Influence the type and dose of organic fertilizer plus the growth of seedlings of cocoa (Theobroma cacao L.) in polybag. This study aims to identify and determine the type and dose of organic fertilizer formula plus the growth of seedlings of cocoa (Theobroma cacao L.) in polybag. This research has been conducted in experimental garden campus of the University of Muhammadiyah Palembang C, Semambu Island Village, District North Inderalaya, Kabupatan Ogan Ilir, South Sumatra Province. This research has been going on from May to July 2015. This study used a randomized block design (RAK) factorial with 12 combined treatment and repeated 3 times with 3 plants examples. The factors examined in the study include the type of formula (J) consisting of: J1 = Formula 1, J2 = formula 2, J3 = 3 and dosage of fertilizer formula (T) consisting of: T1 = 10g / polybag T2 = 20g / polybag T3 = 30g / polybag. The parameters observed in this study was the increase of plant height (cm), in the number of leaves (pieces), root fresh weight (g), root dry weight (g), total wet weight (g), total dry weight (g). The results obtained in this study is a fertilizer treatment of coal formula 3 and dosage 30 g/polybag give the best effect on the growth of seedlings of cocoa (Theobroma cacao L).